Becoming Sacred. The use of body in identity transformation - Šantek, Goran-Pavel (2006)
This paper will analyze various ways of using of the human body and senses in religious practice of the Catholic movement Neocatechumenal Way. This religious movement, established in Spain in 1960s, especially emphasizes ritual practice, which is considered to be the main instrument of communication with the sacred other. Innovations in ritual practice and their symbolic interpretations are followed by careful planning how to achieve full engagement of the members in ritual acts. Namely, the goal of the Neocatechumenal Way is acquiring of the new personality, “ new I” , that needs to be identical to the sacred other. Active, full and whole members' ritual engagement is believed to be a necessary precondition for their successful identity transformation. The ritual of the Neocatechumenal Way requires full and active encounter with the sacred other, contemplative as well as bodily and sensory. Because of that there are various ways of engagement of the human body and physical senses during Neocatechumenal ritual practice. Some examples for using of senses are: for hearing: listening of special songs or experiences of the other members ; for seeing: organization of ritual space, meaningful paintings or total blackout ; for tasting: tasting of symbolic drinks (wine) or food (salt or bread), etc. Examples for meaningful bodily movements (individual or collective) could be: getting up, dancing, nodding, etc. The aim of the paper is to make a contribution, based on new fieldwork data, to the research of bodily and sensory dimensions of ritual practice.
Projekt MZOS
ENG